The effects of the CapZ peptide (TRTK-12) binding to S100B-Ca(2+) as examined by NMR and X-ray crystallography - Charpentier, Thomas H. (2010)
Structure-based drug design is underway to inhibit the S100B-p53 interaction as a strategy for treating malignant melanoma. X-ray crystallography was used here to characterize an interaction between Ca(2+)-S100B and a target, TRTK-12, which binds to the p53 binding site on S100B. The structures of Ca(2+)-S100B (1.5 Å resolution) and S100B-Ca(2+)-TRTK12 (2.0 Å resolution) determined here indicate that the S100B-Ca(2+)-TRTK12 complex is dominated by an interaction between Trp-7 of TRTK-12 and a hydrophobic binding pocket exposed on Ca(2+)-S100B involving residues in helices 2 & 3 and loop 2. As with a S100B-Ca(2+)-p53 peptide complex, TRTK-12 binding to Ca(2+)-S100B was found to increase the proteins Ca(2+) ion binding affinity. One explanation for this effect was that peptide binding introduced a structural change that increased the number of Ca(2+) ligands and/or improved Ca(2+) ion coordination geometry of S100B. This possibility was ruled out when the structures of S100B-Ca(2+)-TRTK12 and S100B-Ca(2+) were compared and calcium ion coordination by the protein was found to be nearly identical in both EF-hand calcium-binding domains (RMSD=0.19). On the other hand, B-factors for residues in EF2 of Ca(2+)-S100B were found to be significantly lowered with TRTK-12 bound. This result is consistent with NMR (15)N relaxation studies that showed that TRTK-12 binding eliminated dynamic properties observed in Ca(2+)-S100B. Such a loss of protein motion may also provide an explanation for how calcium ion binding affinity is increased upon binding a target. Lastly, it follows that any small molecule inhibitor bound to Ca(2+)-S100B would also have to cause an increase in calcium ion binding affinity to be effective therapeutically inside a cell, so these data need to be considered in future drug-design studies involving S100B.